Measurement of the Total-factor Energy Efficiency (TFEE) of China’s Transportation Industry and Its Convergence in Consideration of Carbon Emissions - Yu, Zhaoyu (Journal of power technologies, 2025)
Traditional measures to control environmental pollution in the transportation industry mostly aim to limit carbon emissions and optimize the energy structure while ignoring the improvement in total-factor energy efficiency (TFEE). Effectively alleviating environmental pressure and promoting the high-quality development of the transportation industry within the agreed time range of carbon peak and carbon neutrality are difficult. To effectively address the issues of incomplete measurement indicators for single-factor energy efficiency and ignorance of the temporal association of carbon emissions, this study established an input–output indicator system for the TFEE of China’s transportation industry, which was adopted as the investigation object, in consideration of carbon emissions. The TFEE of China’s transportation industry was measured using the Malmquist–Luenberger index method in consideration of carbon emissions during 2004–2020. Then, the convergence or dispersion of TFEE was analyzed through a convergence model. Results revealed that with carbon emissions considered, the TFEE of China’s transportation industry is 0.959 and presents an east–west–center gradually declining trend. The values of pure technical efficiency, scale efficiency, and technological changes are 1.026, 1.013, and 0.951, respectively. The provincial TFEE differences of the transportation industry have been existing for a long time, but the regions with low energy efficiency are catching up with those with high energy efficiency. The study’s results are valuable for promoting China’s transportation industry, reducing carbon emissions, conserving resources, and boosting the collaborative development of environmental protection and economic growth.